Poetics of visibility in the contemporary Arab American novel - Naous, Mazen (The Ohio State University Press, 2020)
""Redefines dominant perceptions of Arab Americans via an aesthetic analysis of Arab American novels, such as Diana Abu-Jaber's Arabian Jazz and Crescent, Rabih Alameddine's Koolaids: The Art of War, Laila Halaby's Once in a Promised Land, and Mohja Kahf's The Girl in the Tangerine Scarf, thereby launching transcultural possibilities by initiating visibility through poetics"--Provided by publisher"-- Provided by publisher
Keywords: American fiction -- Arab American authors -- History and criticism.; American fiction -- 20th century -- History and criticism.; American fiction -- 21st century -- History and criticism.; Arab Americans in literature.; Marginality, Social, in literature.; Identity (Psychology) in literature.; Roman américain -- 20e siècle -- Histoire et critique.; Roman américain -- 21e siècle -- Histoire et critique.; Américains d'origine arabe dans la littérature.; Identité (Psychologie) dans la littérature.; LITERARY CRITICISM / General; American fiction; American fiction -- Arab American authors; Arab Americans in literature; Identity (Psychology) in literature; Marginality, Social, in literature; 1900-2099; Criticism, interpretation, etc.